The role of noise in clinical environments with particular reference to mental health care: a narrative review - Brown, Brian; Rutherford, Peter; Crawford, Paul (Elsevier, 2015)
Background: There is a large literature suggesting that noise can be detrimental to health and numerous policy documents have promoted noise abatement in clinical settings. Objectives: This paper documents the role of noise in clinical environments and its deleterious effects with a particular focus on mental health care. Our intention however, is to go beyond the notion that noise is simply undesirable and examine the extent to which researchers have explored the meaning of sound in hospital settings and identify new opportunities for research and practice. Data sources and review methods: This is a narrative review which has grouped the literature and issues in the field into themes concerning the general issues of noise in health care; sleep noise and hospital environments; noise in intensive care units; implications for service users and staff; and suggestions for new ways of conceptualising and researching clinical soundscapes. Data sources comprised relevant UK policy documents and the results of a literature search of Pubmed, Scopus and Web of Knowledge using terms such as noise, health, hospital, soundscape and relevant additional terms derived from the papers retrieved. In addition the references of retrieved articles were scanned for additional relevant material and historical items significant in shaping the field. Results: Excess unwanted noise can clearly be detrimental to health and impede recovery, and this is clearly recognised by policymakers especially in the UK context. We use the literature surveyed to argue that it is important also to see the noise in clinical environments in terms of the meaning it conveys and rather than merely containing unwanted sound, clinical environments have a ‘soundscape’. This comprises noises which convey meaning, for example about the activities of other people, the rhythms of the day and the nature of the auditory community of the hospital. Unwanted sound may have unwanted effects, especially on those who are most vulnerable, yet this does not necessarily mean that silence is the better option. Therefore it is our contention that it is important to begin thinking about the social functions of sound in the mental health environment. Conclusions: Whilst it can be stressful, sound can also be soothing, reassuring and a rich source of information about the environment as well. It may be used to secure a degree of privacy for oneself, to exclude others or as a source of solidarity among friends and colleagues. The challenge then is to understand the work that sound does in its ecological context in health care settings.